Collective Bargaining Laws, Threat Effects, and the Determination of Police Compensation - Ichniowski, Casey; Freeman, Richard B.; Lauer, Harrison (Journal of Labor Economics, 1989)
This article demonstrates that state collective bargaining laws are important determinants of union and nonunion public employee compensation. State laws that provide stronger bargaining rights and ensure closure to the bargaining process increase the direct effect of police unions on compensation. Moreover, indirect threat effects on the pay of nonunion police also increase with stronger bargaining laws. In each law category investigated, nonunion police receive most of the compensation premium enjoyed by unionized police. Previous studies that have not adequately controlled for these effects of bargaining laws have therefore underestimated the full effect of public-sector unions on compensation.